Should Atrial Fibrillation Patients With Only 1 Nongender-Related CHA2DS2-VASc Risk Factor Be Anticoagulated?. Issue 7 (July 2016) - Fauchier, Laurent; Clementy, Nicolas; Bisson, Arnaud; Ivanes, Fabrice; Angoulvant, Denis; Babuty, Dominique; Lip, Gregory Y.H.
Abstract : Background and Purpose—: There is some uncertainty about treating patients with atrial fibrillation (AF) with 1 nongender-related (NGR) stroke risk factor (CHA2 DS2 -VASc [ie, congestive heart failure, hypertension, age (≥75 years; 2 points), diabetes, stroke/transient ischemic attack (2 points), vascular disease, age (65–74 years), sex (female)] score of 1 in males and 2 in females) with oral anticoagulation (OAC). Methods—: We investigated adverse outcomes and calculated the net clinical benefit of OAC use in a community-based cohort of unselected AF patients with 0 compared with 1 NGR stroke risk factor (CHA2 DS2 -VASc 0 versus 1 in males; and 1 versus 2 in females). Among 8962 patients with AF, 2208 (25%) had 0 or 1 NGR stroke risk factors, of which 45% were not prescribed OAC. Results—: During a follow-up of 1028±1189 days (median, 495; interquartile range, 5–1882 days), the yearly rate of the combined end point of stroke/systemic embolism in nonanticoagulated AF patients with 1 NGR stroke risk factor was 2.09% (95% confidence interval, 1.37–3.18). This corresponded to an adjusted hazard ratio of 2.82 (95% confidence interval, 1.32–6.04) relative to the group with 0 NGR stroke risk factor. When the benefit of ischemic stroke reduction was balanced against the increased risk of intracranial hemorrhage among patients with 1 NGR stroke risk factor, the net clinical benefit was positive in favor of OAC use versus no antithrombotic therapy or antiplatelet therapy use. The net clinical benefit was negative for antiplatelet therapy use versus no antithrombotic therapy. Conclusions—: Among AF patients with 1 NGR stroke risk factor (ie, CHA2 DS2 -VASc 1 in males or 2 in females), OAC use as indicated according to the guidelines was associated with a positive net clinical benefit for the prevention of stroke and thromboembolic events.